2018
DOI: 10.1101/416628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of correlates of protection against influenza A(H3N2) and A(H1N1)pdm09 infection: Applications to the hospitalized patient population

Abstract: BackgroundInfluenza vaccines are important for prevention of influenza-associated hospitalization. Assessments of serologic correlates of protection can support interpretation of influenza vaccine effectiveness evaluations in hospitalized populations.MethodsSerum specimens collected at admission from adults hospitalized for treatment of acute respiratory illnesses during two influenza seasons were tested in hemagglutination-inhibition (HAI) and neuraminidase-inhibition (NAI) assays. We evaluated the suitabilit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
8
2
Order By: Relevance
“…Adults hospitalized at the University of Michigan Hospital (Ann Arbor, MI, USA) or Henry Ford Hospital (Detroit, MI, USA) were enrolled according to a case definition of within ≤10 days of acute respiratory illness onset and subsequently tested for influenza by reverse transcription-PCR (RT-PCR). Serum specimens collected at hospital admission were obtained for estimation of preinfection/early infection antibodies; 58% of specimens included in this analysis were collected within 3 days of illness onset (42). We analyzed serum samples from 62 hospitalized individuals that had PCR-confirmed H1N1 influenza virus infections.…”
Section: Resultsmentioning
confidence: 99%
“…Adults hospitalized at the University of Michigan Hospital (Ann Arbor, MI, USA) or Henry Ford Hospital (Detroit, MI, USA) were enrolled according to a case definition of within ≤10 days of acute respiratory illness onset and subsequently tested for influenza by reverse transcription-PCR (RT-PCR). Serum specimens collected at hospital admission were obtained for estimation of preinfection/early infection antibodies; 58% of specimens included in this analysis were collected within 3 days of illness onset (42). We analyzed serum samples from 62 hospitalized individuals that had PCR-confirmed H1N1 influenza virus infections.…”
Section: Resultsmentioning
confidence: 99%
“…Adults hospitalized at the University of Michigan Hospital (Ann Arbor, MI, USA) or Henry Ford Hospital (Detroit, MI, USA) were enrolled according to a case definition of within ≤10 days of acute respiratory illness onset and subsequently tested for influenza by RT-PCR. Serum specimens collected at hospital admission were obtained for estimation of pre/early-infection antibodies; 58% of specimens included in this analysis were collected within 3 days of illness onset (41). We analyzed serum samples from 62 hospitalized individuals that had PCR-confirmed H1N1 influenza virus infections.…”
Section: Resultsmentioning
confidence: 99%
“…If our infected participants were making de novo Abs responses, we would anticipate that some of them would have high HAI titers to the infecting H1N1 virus. In addition, Ab titers do not typically increase as days from symptom onset to blood specimen collection increases (41), which suggests that samples used in this study were collected prior to the generation of de novo Ab responses against the infecting virus.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of association between anti-neuraminidase antibody-mediated immunity and protection 271 could explain, in part, the high incidence of infection during the 2017-2018 influenza season. We have 272 previously demonstrated that anti-neuraminidase antibody was not associated with protection during 273 the 2014-2015 season, which was also characterized by high incidence of influenza A(H3N2) infections 274 [26]. Although neuraminidase content is not standardized in influenza vaccines, we observed that anti-275 neuraminidase antibody titers were higher among vaccinated individuals suggesting that some of the 276 existing anti-neuraminidase antibody in this population resulted from vaccination.…”
Section: Discussion 234mentioning
confidence: 84%
“…The serum specimens in this study were collected at a single time point early during acute illness [26]. 295…”
Section: Discussion 234mentioning
confidence: 99%